5 Worlds Book 5: The Emerald Gate - Mark Siegel (Random House, 2022)
Unfortunately, the journey to lighting it on this strange, watery planet is the most dangerous yet. Meanwhile, Stan Moon has one more trick up his sleeve as his frightening powers and mysterious connection to An Tzu continue to grow. How can Oona ever hope to beat him? Can she count on her friends or will a terrible betrayal mean the 5 Worlds will be lost to evil forever?
Keywords: Mystery -- Mystery